Ionomer dispersion having high dispersion stability, method for producing the same, and polymer electrolyte membrane produced using the same
By using resonant acoustic methods and high-pressure treatment in polymer electrolyte fuel cells, the problem of insufficient dispersion stability is solved, the ionic conductivity and durability of the membrane are improved, and the service life of the fuel cell is extended. .
Patent Information
- Application Number
- CN202080068478.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-09-30
- Filing Date
- 2020-09-29
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2040-09-29
AI Technical Summary
In the existing polymer electrolyte fuel cells, due to insufficient dispersion stability of the ionomer dispersion, the ionic conductivity and durability of the polymer electrolyte membrane decrease, which in turn affects the performance and life of the fuel cell.
By adding high-content ionomer solids to the dispersion medium, mixing them using resonance acoustic methods, and combining them with high-voltage treatment, an ionomer dispersion with excellent dispersion stability is prepared, and the ionic conductivity and durability in the polymer electrolyte membrane are optimized. sex.
It improves the ionic conductivity and durability of the polymer electrolyte membrane, extends the service life of the fuel cell, reduces the hydrogen permeability, reduces the generation of free radicals, and thus improves the performance of electrochemical components.
Smart Images

Figure CN114450831B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an ionomer dispersion, a method for preparing the same, and a polymer electrolyte membrane prepared using the same, and more particularly to an ionomer dispersion, a method for preparing the same, and a polymer electrolyte membrane prepared using the same, wherein the ionomer dispersion exhibits excellent dispersion stability despite a high ionomer solid content, thereby optimizing the morphology of the ionomer in the polymer electrolyte membrane and improving the ionic conductivity and durability of the polymer electrolyte membrane. Background Art
[0002] The fuel cell that generates electricity through the combination between hydrogen and oxygen has the advantage that electricity can be continuously generated as long as hydrogen and oxygen are supplied, and the efficiency is about twice that of an internal combustion engine because there is no heat loss.
[0003] Fuel cells emit less pollutants because they convert chemical energy generated by the combination of hydrogen and oxygen directly into electrical energy. Therefore, fuel cells have the advantages of being environmentally friendly and alleviating concerns about resource depletion caused by increased energy consumption.
[0004] The cell stack that actually generates electricity in a fuel cell has a stacked structure of several to dozens of unit cells, each of which includes a membrane-electrode assembly (MEA) and a separator (also called a "bipolar plate"). The membrane-electrode assembly generally includes an anode, a cathode, and an electrolyte membrane interposed between the anode and the cathode.
[0005] According to the type of electrolyte, fuel cells can be classified into alkaline electrolyte fuel cells, polymer electrolyte fuel cells (PEMFC), etc. Among them, polymer electrolyte fuel cells have attracted attention as a portable power source for vehicles and homes due to their advantages of low operating temperature below 100°C, rapid startup, rapid response, and excellent durability.
[0006] Typical examples of polymer electrolyte fuel cells include a proton exchange membrane fuel cell (PEMFC) using hydrogen as fuel, a direct methanol fuel cell (DMFC) using liquid methanol as fuel, and the like.
[0007] For example, in a proton exchange membrane fuel cell (PEMFC), when a fuel such as hydrogen is supplied to the anode, the hydrogen at the anode is oxidized to generate protons (H + ) and electron (e - ). The generated protons are transferred to the cathode through the polymer electrolyte membrane, and the generated electrons are transferred to the cathode through an external circuit. The oxygen supplied to the cathode is combined with the protons and the electrons and thus reduced, thereby generating water.
[0008] Meanwhile, in order to realize the commercialization of fuel cells, requirements related to high performance, long life, etc. should be met. One of the electrochemical elements that has the greatest impact on it is the membrane electrode assembly. In order to improve the dimensional stability of the polymer electrolyte membrane and thus improve its mechanical durability, a reinforced composite membrane-type polymer electrolyte membrane obtained by impregnating a porous support with an ionomer and then coating it has been developed.
[0009] The porous support has the beneficial effect of improving the mechanical strength of the polymer electrolyte membrane, but has the undesirable effect of increasing the resistance of the polymer electrolyte membrane because it is formed of a material that does not have ion transport capability. Therefore, in order to ensure the high performance of the enhanced composite membrane type polymer electrolyte membrane, it is necessary to optimize the morphology of the ionomer present in the porous support.
[0010] Since the hydrophobic backbone and hydrophilic side chains of ionomers have different solubilities, ionomers are usually introduced into and coated on a porous support in the form of a dispersion rather than a solution. Therefore, it is preferred to make the polymer electrolyte membrane as dense as possible by maximizing the concentration of solids in the dispersion.
[0011] However, as the concentration of solids in the dispersion increases, the dispersion stability of the dispersion decreases.
[0012] The reinforced composite membrane-type polymer electrolyte membrane produced from a dispersion having insufficient dispersion stability has a problem of high through-plane resistance (ie, through-plane water channels are not properly formed) due to low impregnation of the dispersion into it.
[0013] Furthermore, the low dispersion stability of the dispersion prevents the ionomer from having a suitable morphology in the polymer electrolyte membrane, thereby resulting in a decrease in the in-plane ionic conductivity of the polymer electrolyte membrane and an increase in the hydrogen permeability of the polymer electrolyte membrane.
[0014] When the hydrogen permeability of the polymer electrolyte membrane is high, the amount of hydrogen gas supplied to the anode and then moved to the cathode via the polymer electrolyte membrane increases. The hydrogen gas moved to the cathode reacts with the oxygen gas supplied to the cathode to generate hydrogen peroxide and free radicals derived therefrom, which causes rapid deterioration of the polymer electrolyte membrane. Summary of the invention
[0015] Technical issues
[0016] Therefore, the present invention has been made in view of the above problems, and relates to an ionomer dispersion, a method for preparing the same, and a polymer electrolyte membrane prepared using the ionomer dispersion.
[0017] One aspect of the present invention is to provide an ionomer dispersion that exhibits excellent dispersion stability despite a high ionomer solids content, thereby optimizing the morphology of the ionomer in a polymer electrolyte membrane and improving both the ionic conductivity and durability of the polymer electrolyte membrane.
[0018] Another aspect of the present invention is to provide a method for preparing an ionomer dispersion which exhibits excellent dispersion stability despite a high ionomer solids content, thereby optimizing the morphology of the ionomer in the polymer electrolyte membrane and improving the ionic conductivity and durability of the polymer electrolyte membrane.
[0019] Another aspect of the present invention is to provide a polymer electrolyte membrane having improved ionic conductivity and durability.
[0020] In addition to the above-mentioned aspects of the present invention, other features and advantages of the present invention will be disclosed in the following detailed description, as will be clearly understood by those skilled in the art to which the present invention belongs.
[0021] Technical Solution
[0022] According to one aspect of the present invention, an ionomer dispersion is provided, comprising: a dispersion medium; and an ionomer solid in the dispersion medium, wherein the concentration of the ionomer solid in the ionomer dispersion is greater than 20 wt %, and the ionomer solid is dispersed at a shear rate of 0.001 s -1 Increase to 1,000s -1 , then from 1,000s -1 Reduced to 0.001s -1 When the viscosity of the ionomer dispersion is measured using a rheometer, the viscosity ratio of the ionomer dispersion defined by the following equation 1 is 1.7 or less:
[0023] *Equation 1: Viscosity ratio = η2 / η1
[0024] Wherein, when the shear rate is increased, η1 is measured when the shear rate is 1s -1 The first viscosity of the ionomer dispersion is when the shear rate is 1s -1 A second viscosity of the ionomer dispersion measured while the shear rate is reduced.
[0025] The first viscosity and the second viscosity may be 1 Pa·s or less.
[0026] At shear rates from 0.001s -1 Increase to 1,000s -1 , then from 1,000s -1 Reduced to 0.001s -1When the shear stress of the ionomer dispersion is measured using a rheometer, the shear stress ratio of the ionomer dispersion defined by the following equation 2 may be 1.5 or less:
[0027] *Equation 2: Shear stress ratio = σ2 / σ1
[0028] Wherein, σ1 is the first shear stress, which is measured when the shear rate is 1s while the shear rate is increasing. -1 , and σ2 is the second shear stress measured while the shear rate is decreasing when the shear rate is 1s -1 The shear stress of the ionomer dispersion is
[0029] The first shear stress and the second shear stress may be 1 Pa·s or less.
[0030] The ionomer solids may comprise fluorinated ionomers, hydrocarbon-based ionomers, or mixtures of the foregoing.
[0031] The ionomer solid may comprise a perfluorosulfonic acid based ionomer (PFSA based ionomer).
[0032] The concentration of ionomer solids in the ionomer dispersion may be from 20 to 50 weight percent.
[0033] According to another aspect of the present invention, a method for preparing an ionomer dispersion is provided, comprising: adding an ionomer to a dispersion medium so that the ionomer solid content is adjusted to be above 20 wt %; and mixing the dispersion medium and the ionomer using a resonant acoustic method.
[0034] The mixing may include applying sonic energy at a frequency of 10 Hz to 100 Hz to the dispersion medium and the ionomer, thereby causing the dispersion medium and the ionomer to resonate at an acceleration of 50 G to 100 G, where G is the acceleration due to gravity.
[0035] Mixing can be performed for 5 minutes to 60 minutes.
[0036] The method may further include applying a pressure of 500 bar to 1,000 bar to the mixture of the dispersion medium and the ionomer obtained by the mixing.
[0037] As the mixture flows, pressure may be applied to the mixture.
[0038] According to another aspect of the present invention, there is provided a polymer electrolyte membrane comprising: a porous support having a plurality of pores; and an ionomer formed by impregnating and coating the porous support with the ionomer dispersion according to any one of claims 1 to 7 and then removing the dispersion medium therefrom.
[0039] According to another aspect of the present invention, there is provided a membrane electrode assembly including: an anode; a cathode; and a polymer electrolyte membrane interposed between the anode and the cathode.
[0040] The general description of the present invention is provided only for the purpose of illustrating the present invention, and not to limit the scope of the present invention.
[0041] Beneficial Effects
[0042] According to the present invention, an ionomer dispersion having high dispersion stability can be prepared by adding an ionomer to a dispersion medium and then mixing by a resonant acoustic method.
[0043] In addition, by applying high pressure to the mixture obtained by mixing based on the resonance acoustic method, the dispersion stability of the ionomer dispersion can be further improved.
[0044] The ionomer dispersion of the present invention exhibits sufficiently high dispersion stability despite having a high ionomer solid content, and can optimize the morphology of the ionomer in the polymer electrolyte membrane, thereby improving both the ionic conductivity and durability of the polymer electrolyte membrane.
[0045] Specifically, the ionomer dispersion of the present invention having high dispersion stability exhibits excellent impregnation performance and has a small and uniform particle size, so that when a reinforced composite membrane-type polymer electrolyte membrane is prepared by impregnating and coating a porous support with the ionomer dispersion, water channels providing hydrogen ion paths can be well formed both in the in-plane and through-plane directions, thereby improving the in-plane and through-plane ionic conductivity of the polymer electrolyte membrane.
[0046] In addition, the ionomer dispersion with high dispersion stability of the present invention has a large reaction surface area, so the crystallinity of the ionomer is effectively improved by the drying and annealing process performed after the dipping / coating process, and the hydrogen permeability of the polymer electrolyte membrane is finally minimized. Therefore, according to the present invention, the generation of free radicals caused by hydrogen permeating the polymer electrolyte membrane and the deterioration of the polymer electrolyte membrane caused thereby can be suppressed, and as a result, the durability of the polymer electrolyte membrane and the electrochemical element (e.g., membrane electrode assembly, fuel cell, etc.) including the polymer electrolyte membrane can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] The accompanying drawings are provided for a better understanding of the present invention and constitute a part of this specification, which illustrate embodiments of the present invention and explain the principles and features of the present invention with reference to the following detailed description, in which:
[0048] Figure 1is a graph showing the viscosity and shear stress of the ionomer dispersion of Example 1a measured while performing a flow sweep;
[0049] Figure 2 is a graph showing the viscosity and shear stress of the ionomer dispersion of Example 2a measured while performing a flow scan; and
[0050] Figure 3 is a graph showing the viscosity and shear stress of the ionomer dispersion of Comparative Example 1a measured while performing a flow scan. DETAILED DESCRIPTION
[0051] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings. However, the embodiments are exemplarily provided only for clear understanding of the present invention, and do not limit the scope of the present invention.
[0052] The ionomer dispersion of the present invention comprises a dispersion medium and ionomer solids dispersed in the dispersion medium.
[0053] The dispersion medium may be water, an organic solvent or a mixture thereof.
[0054] The organic solvent comprises a straight or branched saturated or unsaturated hydrocarbon having 1 to 12 carbon atoms as a main chain (main chain), and comprises at least one selected from the group consisting of alcohol, isopropanol, ketone, aldehyde, carbonate, carboxylate, carboxylic acid, ether and amide. The main chain may include at least a portion of an alicyclic or aromatic cyclic compound.
[0055] The organic solvent may also be N-methylpyrrolidone, dimethyl sulfoxide, tetrahydrofuran or a mixture thereof.
[0056] According to an embodiment of the present invention, the dispersion medium may be a mixture of a hydrophilic organic solvent and water. More specifically, the dispersion medium may be a C1-C 12 A mixture of alcohol and water in a volume ratio of 1:2 to 2:1.
[0057] The ionomer solid may include an ionomer having at least one ion-conducting group selected from the group consisting of a sulfonic acid group, a carboxyl group, a boric acid group, a phosphoric acid group, an imide group, a sulfonimide group, a sulfonamide group, and a sulfonyl fluoride group in a side chain. For example, the ionomer may be a cation conductor having a sulfonic acid group and / or a carboxyl group in a side chain.
[0058] The ionomer may be a fluorinated ionomer, a hydrocarbon-based ionomer, or a mixture thereof.
[0059] For example, the ionomer can be a fluorinated ionomer such as poly(perfluorosulfonic acid) or poly(perfluorocarboxylic acid).
[0060] The hydrocarbon-based ionomer may be a hydrocarbon-based polymer having an ion-conducting group in a side chain [e.g., sulfonated polyimide (S-PI), sulfonated polyarylethersulfone (S-PAES), sulfonated polyetheretherketone (SPEEK), sulfonated polybenzimidazole (SPBI), sulfonated polysulfone (S-PSU), sulfonated polystyrene (S-PS), sulfonated polyphosphazene, sulfonated polyquinoxaline, sulfonated polyketone, sulfonated polyphenylene ether, sulfonated polyethersulfone, sulfonated polyetherketone, sulfonated polyphenylenesulfone, sulfonated polyphenylenesulfide, sulfonated polyphenylenesulfidesulfone, sulfonated polyphenylenesulfidesulfone, sulfonated polyphenylenesulfidesulfonenitrile, sulfonated polyaryleneether, sulfonated polyaryleneethernitrile] ether nitrile), sulfonated polyarylene ether ether nitrile, sulfonated polyarylene ether sulfone ketone, etc.].
[0061] According to an embodiment of the present invention, the ionomer solid may include a perfluorosulfonic acid based ionomer (PFSA based ionomer).
[0062] According to the present invention, in order to produce a polymer electrolyte membrane as dense as possible, the concentration of ionomer solids in the ionomer dispersion is 20 wt % or more. For example, the concentration of ionomer solids in the ionomer dispersion may be 20 wt % to 50 wt %.
[0063] Optionally, the ionomer dispersion may further comprise a radical scavenger capable of decomposing and / or removing peroxides (e.g., hydrogen peroxide) and free radicals (e.g., hydrogen radicals) which are generated during redox reactions in fuel cells and lead to degradation of the polymer electrolyte membrane (more specifically, the ionomer) and the catalyst electrode.
[0064] For example, the ionomer dispersion may further comprise at least one free radical scavenger selected from the group consisting of transition metals, such as Ce, Ni, W, Co, Cr, Zr, Y, Mn, Fe, Ti, V, Mo (molybdenum), La (lanthanum) and Nd (neodymium); noble metals, such as Au, Pt, Ru, Pd and Rh; ions of the foregoing; oxides of the foregoing; and salts of the foregoing.
[0065] According to the present invention, at a shear rate of 0.001s -1 Increase to 1,000s -1 , then from 1,000s -1 Reduced to 0.001s -1 When a flow scan is performed by measuring the viscosity of the ionomer dispersion using a rheometer while performing the flow scan, the viscosity ratio of the ionomer dispersion defined by the following equation 1 is 1.7 or less, preferably 0.5 to 1.5, more preferably 0.7 to 1.3, and even more preferably 0.9 to 1.1:
[0066] *Equation 1: Viscosity ratio = η2 / η1
[0067] Where η1 is measured when the shear rate increases. -1 The first viscosity of the ionomer dispersion when the shear rate is reduced is η2, which is measured when the shear rate is 1s -1 The second viscosity of the ionomer dispersion.
[0068] That is, the viscosity ratio is a parameter indicating the dispersion stability of the ionomer dispersion, and as the viscosity ratio becomes closer to 1 (ie, as the difference between the first viscosity and the second viscosity decreases), the dispersion stability of the ionomer dispersion increases.
[0069] An example of a rheometer for performing flow scanning to measure the viscosity ratio is Discovery HR-3 produced by TA Instruments, and the measurement conditions are as follows.
[0070] * Temperature: 25℃
[0071] * Soaking time: 0.0 seconds
[0072] *Waiting temperature: Off
[0073] *Logarithmic scan
[0074] * Shear rate: 1.0·e -3 ~10 3 (s -1 )
[0075] *Points per decade: 5
[0076] *Equilibrium time: 1.0 seconds
[0077] *Average time: 1.0 seconds
[0078] According to an embodiment of the present invention, both the first viscosity and the second viscosity may be 1 Pa·s or less.
[0079] In addition, according to an embodiment of the present invention, when the shear stress of the ionomer dispersion is measured while performing the flow scan, the shear stress ratio of the ionomer dispersion defined by the following Equation 2 may be 1.5 or less:
[0080] *Equation 2: Shear stress ratio = σ2 / σ1
[0081] Where σ1 is the first shear stress, which is measured when the shear rate increases. -1 σ2 is the shear stress of the ionomer dispersion, and σ2 is the second shear stress, which is measured when the shear rate decreases. -1 Shear stress of ionomer dispersion.
[0082] That is, the viscosity ratio is a primary parameter indicating the dispersion stability of the ionomer dispersion, while the shear stress ratio is a secondary parameter indicating the dispersion stability of the ionomer dispersion. That is, as the shear stress ratio becomes closer to 1 (i.e., as the difference between the first shear stress and the second shear stress decreases), the dispersion stability of the ionomer dispersion increases. It is ideal that the shear stress ratio is 1.
[0083] According to an embodiment of the present invention, both the first shear stress and the second shear stress may be 1·Pa or less.
[0084] Hereinafter, a method for preparing an ionomer dispersion according to an embodiment of the present invention will be described in detail.
[0085] The method for preparing the ionomer dispersion of the present invention comprises adding the ionomer into a dispersion medium and mixing the dispersion medium with the ionomer.
[0086] As described above, since the hydrophobic main chain and the hydrophilic side chain of the ionomer have different solubilities, the ionomer is usually introduced into the porous support in the form of a dispersion rather than a solution and coated thereon. Therefore, according to the present invention, by adding the ionomer to the dispersion medium so that the ionomer dispersion contains a large amount of ionomer solids of 20% by weight or more, a dense polymer electrolyte membrane can be manufactured.
[0087] However, in order to overcome the problem that the dispersion stability of the dispersion decreases as the concentration of solids in the dispersion increases, a resonant acoustic method is used to mix the dispersion medium and the ionomer.
[0088] Mixing based on the resonant acoustic method may be performed by applying acoustic energy having a frequency of 10 Hz to 100 Hz to the dispersion medium to which the ionomer is added so that the dispersion medium and the ionomer resonate at an acceleration of 50 G to 100 G, where G is the acceleration of gravity.
[0089] Mixing based on the resonant acoustic method is performed, for example, using a mixer commercially available from Resodyn Acoustic Mixers, Inc. (model: LabRAMII).
[0090] The mixing based on the resonant acoustic method may be performed for, for example, 5 minutes to 60 minutes.
[0091] By adding the ionomer to the dispersion medium and then mixing using a resonant acoustic method, an ionomer dispersion can be prepared that has high dispersion stability despite the high ionomer solids content.
[0092] According to an embodiment of the present invention, the method may further include applying a high pressure of 500 to 1,000 bar to the mixture of the dispersion medium and the ionomer obtained by mixing. For example, pressurization may be performed using a homogenizer, and the high pressure may be applied to the mixture flowing in the homogenizer.
[0093] Optionally, in order to further improve the dispersion stability of the ionomer dispersion, the high-pressure dispersion using a homogenizer may be repeated 2 to 5 times.
[0094] As the particle size becomes smaller and more uniform due to pressurization, the dispersion stability of the ionomer dispersion is further improved.
[0095] In addition, since the particle size is small and uniform, the ionomer is given a large reaction surface area, so the crystallinity of the ionomer can be effectively improved through the drying and / or annealing process, and as a result, the hydrogen permeability of the polymer electrolyte membrane can be minimized. Therefore, the generation of free radicals due to hydrogen permeation into the polymer electrolyte membrane and the degradation of the polymer electrolyte membrane can be suppressed, and as a result, the durability of the polymer electrolyte membrane and the electrochemical component (e.g., membrane electrode assembly, fuel cell, etc.) including the polymer electrolyte membrane can be improved.
[0096] The polymer electrolyte membrane of the present invention can be produced by impregnating and coating a porous support having a plurality of pores with the ionomer dispersion of the present invention prepared as described above, followed by removing the dispersion medium.
[0097] Hereinafter, a method of manufacturing a polymer electrolyte membrane according to an embodiment of the present invention will be described in detail.
[0098] The porous support may be formed of polytetrafluoroethylene (PTFE) or of tetrafluoroethylene and CF2=CFC nF 2n+1 (where n is an integer from 1 to 5) or CF2=CFO-(CF2CF(CF3)O) m C n F 2n+1 (wherein m is an integer from 0 to 15, and n is an integer from 1 to 15) is formed.
[0099] For example, an e-PTFE porous carrier in the form of an expanded membrane can be formed by extruding PTFE on a strip in the presence of a lubricant, followed by expansion and heat treatment. Additional expansion and heat treatment can be further performed after the heat treatment. By controlling the expansion and heat treatment, an e-PTFE porous carrier with various microstructures can be formed. For example, the e-PTFE porous carrier can have a microstructure in which nodes are connected to each other by fibrils or a microstructure consisting only of fibrils.
[0100] Alternatively, the porous carrier may be a nonwoven web. The nonwoven web may be formed from a carrier-forming liquid comprising at least one hydrocarbon-based polymer selected from the group consisting of polyolefins (e.g., polyethylene, polypropylene, polybutylene, etc.), polyesters (e.g., PET, PBT, etc.), polyamides (e.g., nylon 6, nylon 6,6, aramid, etc.), polyamic acid (converted to polyimide by imidization after forming into a web), polyurethane, polybutylene, polylactic acid, polyvinyl alcohol, polyphenylene sulfide (PPS), polysulfone, liquid crystal polymer, polyethylene-co-vinyl acetate, polyacrylonitrile, cyclic polyolefins, polyoxymethylene, and polyolefin-based thermoplastic elastomers.
[0101] The nonwoven web may be produced by any one method selected from the group consisting of wet-laid, electrospinning, carding, garnetizing, air-laid, melt-blown, spunbonded, and stitch bonding.
[0102] The porous support that can be used in the present invention may have an average pore diameter of 0.1 μm to 0.2 μm and a porosity of 60% to 95%.
[0103] When the average pore size is less than 0.1 μm or the porosity is less than 60%, the resistance of the polymer electrolyte membrane increases and the ion conductivity decreases due to the small amount of ionomer in the porous support. On the other hand, when the average pore size is greater than 0.2 μm or the porosity is greater than 95%, the subsequent processing may not be smoothly performed due to the deterioration of the shape stability of the polymer electrolyte membrane.
[0104] Optionally, in order to further improve the mechanical strength of the polymer electrolyte membrane and allow all pores in the porous support to be fully filled with the ionomer, two or more relatively thin porous supports may be used instead of one thick porous support.
[0105] When preparing a porous support, the porous support is impregnated and coated with the ionomer dispersion of the present invention. The impregnation and coating can be performed by (i) casting the ionomer dispersion on a substrate and then soaking the porous support with the ionomer dispersion, or (ii) coating the porous support with the ionomer dispersion. For example, the coating can be performed using rod coating, comma coating, slot die coating, screen printing, spray coating, doctor blade coating, etc.
[0106] Then, drying for removing the dispersion medium from the ionomer dispersion and annealing for increasing the crystallinity of the ionomer are sequentially performed.
[0107] Drying may be performed at 60° C. to 150° C. for 30 minutes to 2 hours. When the drying temperature is lower than 60° C. or the drying time is less than 30 minutes, the dispersion medium may not escape, and thus a dense polymer electrolyte membrane may not be formed.
[0108] Optionally, drying may be performed in multiple steps while increasing the temperature within the drying temperature range.
[0109] Annealing may be performed at 150° C. to 190° C. for 3 minutes to 1 hour. When the annealing temperature is higher than 190° C. or the annealing time is longer than 1 hour, there is a problem that the ion conductive groups of the ionomer decompose and the performance of the polymer electrolyte membrane deteriorates.
[0110] According to an embodiment of the present invention, there are provided a membrane-electrode assembly including the polymer electrolyte membrane manufactured as described above and a fuel cell including the membrane-electrode assembly.
[0111] Specifically, the membrane-electrode assembly includes an anode, a cathode and a polymer electrolyte membrane interposed therebetween. Except for using the polymer electrolyte membrane according to the present invention as the polymer electrolyte membrane, the membrane-electrode assembly is the same as a conventional membrane-electrode assembly for a fuel cell, so a detailed description thereof will be omitted herein.
[0112] In addition, the fuel cell is the same as a conventional fuel cell except for including the membrane-electrode assembly of the present invention, and thus a detailed description thereof will be omitted herein.
[0113] Hereinafter, the present invention will be described in more detail with reference to specific examples. However, the following examples are provided only for a better understanding of the present invention and should not be construed as limiting the scope of the present invention.
[0114] [Preparation of ionomer dispersion]
[0115] Example 1a
[0116] The PFSA-based ionomer (EW 725) was added to a dispersion medium in which 1-propanol and water were mixed in a weight ratio of 55:45, so that the ionomer solid content was adjusted to 20 wt %. Then, the dispersion medium and the ionomer were mixed (i.e., mixed using a resonant acoustic method) using a mixer (Resodyn Acoustic Mixers, Inc., LabRAM II) at room temperature and humidity with an acceleration of 90 G to induce resonance for 20 minutes to prepare an ionomer dispersion.
[0117] Example 2a
[0118] The PFSA-based ionomer (EW 725) was added to a dispersion medium in which 1-propanol and water were mixed in a weight ratio of 30:40, so that the ionomer solid content was adjusted to 30% by weight. Then, the dispersion medium and the ionomer were mixed using a mixer (Resodyn AcousticMixers, Inc., LabRAM II) at room temperature and humidity with an acceleration of 90G to cause resonance for 20 minutes. Then, a high-pressure dispersion of 600 bar high pressure was applied to the mixture of the dispersion medium and the ionomer using a homogenizer, and repeated 3 times to prepare an ionomer dispersion.
[0119] Example 3a
[0120] An ionomer dispersion was prepared in the same manner as in Example 1a, except that a PFSA-based ionomer (EW 725) was added to a dispersion medium of 1-propanol and water mixed in a weight ratio of 49:51 such that the ionomer solid content was adjusted to 30 wt %.
[0121] Comparative Example 1a
[0122] A PFSA-based ionomer (EW 725) was added to a dispersion medium in which 1-propanol and water were mixed in a weight ratio of 55:45, so that the ionomer solid content was adjusted to 20 wt %. Then, the dispersion medium and the ionomer were mixed using a magnetic stirrer at 250 rpm for 48 hours to cause resonance at room temperature and humidity to prepare an ionomer dispersion.
[0123] Comparative Example 2a
[0124] PFSA-based ionomer (EW 725) was added to a dispersion medium in which 1-propanol and water were mixed at a weight ratio of 47:53 so that the ionomer solid content was adjusted to 25 wt %. Then, the dispersion medium and ionomer were mixed using a magnetic stirrer at 50° C. at 250 rpm for 48 hours to prepare an ionomer dispersion.
[0125] [Evaluation of dispersion stability of ionomer dispersion]
[0126] The dispersion stability of the ionomer dispersions prepared in the examples and comparative examples was evaluated while performing flow scanning. Specifically, the ... -1 Increase to 1,000s -1 , then from 1,000s -1 Reduced to 0.001s -1 At the same time, the viscosity and shear stress of the ionomer dispersion were measured using a "Discovery HR-3" rheometer from TA Instruments under the following conditions.
[0127] * Temperature: 25℃
[0128] * Soaking time: 0.0 seconds
[0129] *Waiting temperature: Off
[0130] *Logarithmic scan
[0131] * Shear rate: 1.0 e -3 ~10 3 (s -1 )
[0132] *Points per decade: 5
[0133] *Equilibrium time: 1.0 seconds
[0134] *Average time: 1.0 seconds
[0135] The viscosity ratio of the ionomer dispersion defined by the following equation 1 and the ionomer shear stress ratio defined by the following equation 2 were calculated, and the results are shown in Table 1.
[0136] *Equation 1: Viscosity ratio = η2 / η1
[0137] *Equation 2: Shear stress ratio = σ2 / σ1
[0138] Where η1 and σ1 represent the shear rate at 1s measured while the shear rate increases. -1 , η2 and σ2 are the viscosity and shear stress of the ionomer dispersion when the shear rate is 1s -1 Viscosity and shear stress of ionomer dispersions.
[0139] [Table 1]
[0140] η1(Pa·s) η2(Pa·s) η2 / η1 σ1(Pa) σ2(Pa) σ2 / σ1 Example 1a 0.402 0.507 1.26 0.400 0.434 1.09 Example 2a 0.226 0.228 1.01 0.226 0.228 1.01 Example 3a 0.620 0.965 1.56 0.625 0.875 1.40 Comparative Example 1a 0.515 3.000 5.83 0.523 1.305 2.50 Comparative Example 2a 0.610 1.067 1.75 0.605 0.968 1.60
[0141] Figures 1 to 3] are graphs showing the viscosity and shear stress of the ionomer dispersions of Example 1a, Example 2a, and Comparative Example 1a, respectively, measured while performing flow scans.
[0142] from Figure 1 It can be seen from the Figure and Table 1 that, in the ionomer dispersion of Example 1a prepared by the resonant acoustic method, the viscosity and shear stress measured while the shear rate increases are very similar to the viscosity and shear stress measured while the shear rate decreases, and the viscosity ratio and shear stress ratio defined by Equation 1 and Equation 2, respectively, are less than 1.3, which means that the ionomer dispersion of Example 1a exhibits very high dispersion stability.
[0143] from Figure 2 It can be seen from the Figure and Table 1 that, in the ionomer dispersion of Example 2a prepared by additionally performing a high-pressure dispersing process after a mixing process based on a resonant acoustic method, the viscosity and shear stress measured while the shear rate is increased are substantially the same as those measured while the shear rate is decreased, and the viscosity ratio and the shear stress ratio defined by Equation 1 and Equation 2, respectively, reach approximately 1, which means that the ionomer dispersion of Example 2a exhibits the greatest dispersion stability.
[0144] As shown in Table 1, the ionomer dispersion of Example 3a, which contains a higher amount of ionomer solids, exhibits higher viscosity ratio and shear stress ratio than Example 1a, but because it is prepared by the same mixing procedure based on the resonant acoustic method as Example 1a, it exhibits a low viscosity ratio of less than 1.7 (i.e., 1.56) and a low shear stress ratio of less than 1.5 (i.e., 1.40).
[0145] At the same time, from Figure 3 It can be seen from Figure 1 and Table 1 that, in the ionomer dispersion of Comparative Example 1a prepared by a mixing process using a conventional magnetic stirrer, the viscosity and shear stress measured while the shear rate is increased are significantly different from the viscosity and shear stress measured while the shear rate is decreased, and the dispersion stability of the ionomer dispersion is very low, so that the viscosity ratio and the shear stress ratio defined by Equation 1 and Equation 2, respectively, are higher than 2.
[0146] On the other hand, the ionomer dispersion of Comparative Example 2a prepared by performing mixing at a higher temperature exhibited lower viscosity ratio and shear stress ratio than those of Comparative Example 1a, but because it was prepared through a mixing procedure using a conventional magnetic stirrer like Comparative Example 1a, it exhibited a high viscosity ratio exceeding 1.7 (i.e., 1.75) and a high shear stress ratio exceeding 1.5 (i.e., 1.60).
[0147] [Manufacturing of polymer electrolyte membrane]
[0148] Example 1b
[0149] Two e-PTFE porous supports each having an average pore size of 0.15 μm and a porosity of 75% were stacked, and the ionomer dispersion of Example 1a was applied to the upper and lower surfaces thereof. Subsequently, the resulting structure was sequentially subjected to drying and annealing processes to manufacture a reinforced composite membrane-type polymer electrolyte membrane. The drying process was performed at 80° C. for 1 hour, and the annealing process was performed at 180° C. for 10 minutes.
[0150] Example 2b
[0151] A polymer electrolyte membrane was manufactured in the same manner as in Example 1b, except that the ionomer dispersion of Example 2a was used instead of the ionomer dispersion of Example 1a.
[0152] Example 3b
[0153] A polymer electrolyte membrane was manufactured in the same manner as in Example 1b, except that the ionomer dispersion of Example 3a was used instead of the ionomer dispersion of Example 1a.
[0154] Comparative Example 1b
[0155] A polymer electrolyte membrane was manufactured in the same manner as in Example 1b, except that the ionomer dispersion of Comparative Example 1a was used instead of the ionomer dispersion of Example 1a.
[0156] Comparative Example 2b
[0157] A polymer electrolyte membrane was manufactured in the same manner as in Example 1b, except that the ionomer dispersion of Comparative Example 2a was used instead of the ionomer dispersion of Example 1a.
[0158] [Measurement of polymer electrolyte membrane characteristics]
[0159] The (i) in-plane ionic conductivity, (ii) water absorption, (iii) through-plane resistance and (iv) hydrogen permeability of the polymer electrolyte membranes of the Examples and Comparative Examples were measured according to the following methods. The results are shown in Table 2.
[0160] In-plane ionic conductivity and water absorption
[0161] The in-plane ionic conductivity and water absorption of the polymer electrolyte membrane were measured at 80° C. and 50 RH %, respectively, using a magnetic suspension balance apparatus (Bell Japan).
[0162] Through-plane resistor
[0163] The through-plane resistance of the polymer electrolyte membrane at 80° C. and 50 RH % was measured using a membrane testing system (model name: MTS 740) by Scribner.
[0164] Hydrogen permeability
[0165] The hydrogen permeability of the polymer electrolyte membrane was measured at 65° C. and 50 RH % using gas chromatography.
[0166] [Table 2]
[0167]
[0168] As can be seen from Table 2, the polymer electrolyte membranes of Examples 1b and 2b manufactured using an ionomer dispersion having high dispersion stability exhibit the same water absorption as the polymer electrolyte membrane of Comparative Example 1b manufactured using an ionomer dispersion having low dispersion stability, but exhibit (i) higher in-plane ionic conductivity, (ii) lower through-plane resistance, and (iii) lower hydrogen permeability.
[0169] In addition, the polymer electrolyte membrane of Example 2b is manufactured using the ionomer dispersion of Example 2a that is endowed with the greatest dispersion stability by additionally performing a high-pressure dispersion process in addition to the mixing process based on the resonant acoustic method of the present invention. The polymer electrolyte membrane of Example 2b exhibits the best in-plane ionic conductivity and through-plane ionic conductivity and the best hydrogen permeability (i.e., the lowest hydrogen permeability).
[0170] On the other hand, the polymer electrolyte membrane of Example 3b manufactured using the ionomer dispersion of Example 3a (which has a viscosity ratio slightly lower than 1.7 (i.e., 1.56) and a shear stress ratio slightly lower than 1.5 (i.e., 1.40)) also exhibited excellent physical properties in terms of ionic conductivity and hydrogen permeability, although lower than those of the polymer electrolyte membranes of Examples 1b and 2b.
[0171] In contrast, the polymer electrolyte membrane of Example 3b manufactured using the ionomer dispersion of Example 3a having a viscosity ratio slightly higher than 1.7 (i.e., 1.75) and a shear stress ratio slightly higher than 1.5 (i.e., 1.60) exhibited inferior physical properties to those of the polymer electrolyte membrane of Example 3b. Specifically, the hydrogen permeability of the polymer electrolyte membrane of Example 3b was at least twice that of the polymer electrolyte membrane of Example 3b. This indicates that the polymer electrolyte membrane manufactured using an ionomer dispersion having a viscosity ratio higher than 1.7 and / or a shear stress ratio higher than 1.5 did not exhibit satisfactory ionic conductivity or hydrogen permeability.
Claims
1. An ionomer dispersion comprising: Dispersion medium; as well as an ionomer solid in the dispersion medium, the ionomer solid comprising (i) a fluorinated ionomer selected from the group consisting of poly(perfluorosulfonic acid) and poly(perfluorocarboxylic acid), (ii) a hydrocarbyl ionomer selected from the group consisting of sulfonated polyimide, sulfonated polyarylethersulfone, sulfonated polyetheretherketone, sulfonated polybenzimidazole, sulfonated polysulfone, sulfonated polystyrene, sulfonated polyphosphazene, sulfonated polyquinoxaline, sulfonated polyketone, sulfonated polyphenylene ether, sulfonated polyethersulfone, sulfonated polyetherketone, sulfonated polyphenylene sulfide, sulfonated polyphenylene sulfide sulfone, sulfonated polyphenylene sulfide sulfone nitrile, sulfonated polyarylene ether, sulfonated polyarylene ether nitrile, sulfonated polyarylene ether ether nitrile and sulfonated polyarylene ether sulfone ketone, or (iii) a mixture of the fluorinated ionomer and the hydrocarbyl ionomer, wherein the concentration of the ionomer solid in the ionomer dispersion is 20 wt % or more, and At shear rates from 0.001s -1 Increase to 1000s -1 Then from 1000s -1 Reduced to 0.001s -1 When the viscosity of the ionomer dispersion is measured using a rheometer, the viscosity ratio of the ionomer dispersion defined by the following equation 1 is 1.7 or less: *Equation 1: Viscosity ratio = η2 / η1 Wherein, η1 is measured while the shear rate increases when the shear rate is 1s -1 The first viscosity of the ionomer dispersion is η2 is measured while the shear rate is decreasing. When the shear rate is 1s -1 The second viscosity of the ionomer dispersion is .
2. The ionomer dispersion according to claim 1, wherein The first viscosity and the second viscosity are 1 Pa·s or less.
3. The ionomer dispersion according to claim 1, wherein At the shear rate from 0.001s -1 Increase to 1000s -1 Then from 1000s -1 Reduced to 0.001s -1 When the shear stress of the ionomer dispersion is measured using a rheometer, the shear stress ratio of the ionomer dispersion defined by the following equation 2 is 1.5 or less: *Equation 2: Shear stress ratio = σ2 / σ1 Wherein, σ1 is the first shear stress, which is measured while the shear rate is increasing. When the shear rate is 1s -1 , and σ2 is a second shear stress measured while the shear rate is decreasing when the shear rate is 1 s -1 The shear stress of the ionomer dispersion is 4. The ionomer dispersion according to claim 3, wherein The first shear stress and the second shear stress are 1 Pa·s or less.
5. The ionomer dispersion according to claim 1, wherein The ionomer solid comprises a perfluorosulfonic acid based ionomer (PFSA based ionomer).
6. The ionomer dispersion according to claim 1, wherein The concentration of the ionomer solids in the ionomer dispersion is from 20 wt % to 50 wt %.
7. A method for preparing an ionomer dispersion, comprising: adding an ionomer to the dispersion medium so that the ionomer solid content is adjusted to be greater than 20 wt %; mixing the dispersion medium with the ionomer using a resonant acoustic method; as well as applying a pressure of 500 bar to 1000 bar to the mixture of the dispersion medium and the ionomer obtained by the mixing, wherein the ionomer is (i) a fluorinated ionomer selected from the group consisting of poly(perfluorosulfonic acid) and poly(perfluorocarboxylic acid), (ii) a hydrocarbon-based ionomer selected from the group consisting of sulfonated polyimide, sulfonated polyarylethersulfone, sulfonated polyetheretherketone, sulfonated polybenzimidazole, sulfonated polysulfone, sulfonated polystyrene, sulfonated polyphosphazene, sulfonated polyquinoxaline, sulfonated polyketone, sulfonated polyphenylene ether, sulfonated polyethersulfone, sulfonated polyetherketone, sulfonated polyphenylene sulfide, sulfonated polyphenylene sulfide sulfone, sulfonated polyphenylene sulfide nitrile, sulfonated polyarylene ether, sulfonated polyarylene ether nitrile, sulfonated polyarylene ether ether nitrile and sulfonated polyarylene ether sulfone ketone, or (iii) a mixture of the fluorinated ionomer and the hydrocarbon-based ionomer.
8. The method according to claim 7, wherein: The mixing includes applying acoustic energy with a frequency of 10 Hz to 100 Hz to the dispersion medium and the ionomer, so that the dispersion medium and the ionomer resonate with an acceleration of 50 G to 100 G, wherein G is gravitational acceleration.
9. The method according to claim 7, wherein: The mixing is performed for 5 to 60 minutes.
10. The method according to claim 7, wherein: The pressure is applied to the mixture while the mixture flows.
11. A polymer electrolyte membrane comprising: a porous carrier having a plurality of pores; as well as An ionomer formed by impregnating and coating the porous support with the ionomer dispersion according to any one of claims 1 to 6 and then removing the dispersion medium from the ionomer dispersion.
12. A membrane electrode assembly comprising: anode; cathode; as well as The polymer electrolyte membrane according to claim 11, wherein the polymer electrolyte membrane is interposed between the anode and the cathode.
